Orbital anisotropy of magnetically distorted superfluid 3He- B - Gongadze, A.; Kharadze, G.; Vachnadze, G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1997)
The orbital anisotropy of the magnetized superfluid B-phase of liquid 3He is investigated theoretically for arbitrary fields and temperatures. The behavior of freely rotating B-phase under the action of magnetic field is considered.